Three-dimensional visualization of fossil flowers, fruits, seeds, and other plant remains using synchrotron radiation X-ray tomographic microscopy (SRXTM): new insights into Cretaceous plant diversity. (July 2014) - Friis, Else Marie; Marone, Federica; Pedersen, Kaj Raunsgaard; Crane, Peter R.; Stampanoni, Marco
Abstract : The application of synchrotron radiation X-ray tomographic microscopy (SRXTM) to the study of mesofossils of Cretaceous age has created new possibilities for the three-dimensional visualization and analysis of the external and internal structure of critical plant fossil material. SRXTM provides cellular and subcellular resolution of comparable or higher quality to that obtained from permineralized material using thin sections or the peel technique. SRXTM also has the advantage of being non-destructive and results in the rapid acquisition of large quantities of data in digital form. SRXTM thus refocuses the effort of the investigator from physical preparation to the digital post-processing of X-ray tomographic data, which allows great flexibility in the reconstruction, visualization, and analysis of the internal and external structure of fossil material in multiple planes and in two or three dimensions. A review of recent applications in paleobotany demonstrates that SRXTM will dramatically expand the level of information available for diverse fossil plants. Future refinement of SRXTM approaches that further increases resolution and eases digital post-processing, will transform the study of mesofossils and create new possibilities for advancing paleobotanical knowledge. We illustrate these points using a variety of Cretaceous mesofossils, highlighting in particular those cases where SRXTM has been essential for resolving critical structural details that have enhanced systematic understanding and improved phylogenetic interpretations.